Inaugural Address (The Pakistan Development Review, 2006)
Excellencies, Distinguished Guests, Ladies and Gentlemen, Assalam-o-Alaikum and Good Morning It is a privilege to be in your midst today in the Annual General Meeting and Conference of the Pakistan Society of Development Economists. This is the fourth time in my seven years of public life here that I have the opportunity of interacting with such a distinguished gathering of economists, academicians, and scholars at this forum. I cannot help but think about my first interaction with this gathering 7 years ago. It was the 15th AGM of PSDE in November 1999. I had assumed responsibility as Finance Minister a few weeks ago and I took the opportunity to present a roadmap to this very audience. I am happy to return today to tell you what we have been able to achieve, the challenges we face and our plans for the future. I expect you—the research community— to help us in preparing better policies to support the progress that we have made so far. The economists present here know the story of our progress intimately so I will not go into any details. You would recall that seven years ago, our country was in the middle of a major crisis. Our economy was in dire straits. The state of governance left much to be desired. We were also isolated with mounting tensions on our borders. We have come a long way since then!